Meanings on research methodology in doctoral programs in education. An exploration from its curricular component - Jiménez Mora, José (2023)
This article discusses the various meanings attributed to the concept of research methodology, based on an analysis of the study plans and programs of three doctoral programs in education in Mexico. These programs have well-established faculty and have produced several generations of trained students. The article outlines the methodology used to analyze the curricular discourse related to the concept of research methodology, and presents findings that highlight the different interpretations given to key elements of this concept across the three programs. The results reveal nine major attributions of meaning to the concept of research methodology, with varying degrees of similarity across the three programs. One shared conception is that research methodology is primarily a logic of knowledge generation, rather than a set of techniques. Additionally, all three programs acknowledge that research methodology is an object of knowledge and training that is constantly evolving. Overall, this article provides valuable insights into the ways in which research methodology is understood and taught in academic settings, particularly within the context of doctoral programs in education. The use of a comparative approach allows for a deeper understanding of the nuances and differences in meaning that exist across different programs.The article is relevant to scholars and educators interested in research methodology and its role in training for educational research.